Comparison of the corneal curvatures obtained from three different keratometers - Magar, JB Ale (Nepalese Journal of Ophthalmology, 2013)
Introduction: Keratometry forms an important component of the biometry for a calculation of the intraocular lens power and selecting a contact lens’ parameters. Objective: To investigate the agreement between three different keratometers commonly used in an ophthalmology clinic. Materials and methods: In this prospective study, keratometry was performed using an IOL Master (IM), a manual keratometer (Man) and a autokeratometer (Top) in twenty five eyes of thirteen volunteer subjects. The average keratometry values and corneal astigmatism (J180 and J45 components) were computed and compared. The agreements between the instruments were analysed using the Bland Altman statistical method. The main outcome measures are average keratometry values and corneal astigmatism. Results: The mean of average keratometry values obtained from the IOL Master, manual keratometry and autokeratometry were 44.388 ± 1.430, 44.297 ± 1.425 and 44.220 ± 1.497 D, respectively. The mean difference in the average keratometry between the instruments were 0.31 ± 0.09 for IM and Man (p = 0.012), 0.14 ± 0.17 for IM and Top (p = < 0.001) and 0.29 ± 0.77 for Man and Top (p = 0.26). The mean differences in the J180 component of astigmatism were: 0.02 ± 0.11 for IM and Man, 0.02 ± 0.09 for IM and Top, and - 0.01 ± 0.11 for Man and Top. Similarly, for the J45 component, the mean differences were 0.02 ± 0.12 for IM and Man, 0.01 ± 0.13 for IM and Top and - 0.02 ± 0.10 for Man and Top. Conclusion: Average keratometry values obtained from different instruments vary significantly. The IOL Master consistently over-estimated the corneal power compared to the manual and the autokeratometer. All three instruments provided similar estimation of the corneal astigmatism. Nepal J Ophthalmol 2013; 5(9):9-15 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7815